Challenges and Issues In Quality Education: Addressing Challenges and Issues in Quality Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Today, education faces multiple challenges in terms ofdemand, supply, quality and returns, both for providers and the clienteleconcerned. The education system, from the highest levels down to the classroom,needs to deliver the knowledge and skills that students need, and to respond asthose needs change. Quality tools and processes can help in this juncture.Education in India falls under the control of both the Union Government and thestates, with some responsibilities lying with the Union and the states havingautonomy for others. The factors that influence the big issues and challenge inturn contribute to the poor credibility of teacher education. This paperanalyses some aspects of the issues and challenges in quality Educationfocusing on Liability, Coalition, Assessment, Shortage of Teachers andDeclining Enrolment in Traditional Fields of Knowledge, Red Tapism and GlobalCompetition.